Targeting Bcl-2 Proteins in Acute Myeloid Leukemia - Wei, Yunxiong; Cao, Yaqing; Sun, Rui; Cheng, Lin; Xiong, Xia; Jin, Xin; He, Xiaoyuan; Lu, Wenyi; Zhao, Mingfeng (Frontiers in Oncology, 2020)
B cell lymphoma 2 (BCL-2) family proteins play an important role in intrinsic apoptosis. Overexpression of BCL-2 proteins in acute myeloid leukemia can circumvent resistance to apoptosis and chemotherapy. Considering this effect, the exploration of anti-apoptotic BCL-2 inhibitors is considered to have tremendous potential for the discovery of novel pharmacological modulators in cancer. This review outlines the impact of BCL-2 family proteins on intrinsic apoptosis and the development of acute myeloid leukemia (AML). Furthermore, we will also review the new combination therapy with venetoclax that overcomes resistance to venetoclax and discuss biomarkers of treatment response identified in early-phase clinical trials.